The discovery of the Flammer syndrome: a historical and personal perspective - Flammer, Josef (EPMA J, 2017)
This review describes the clinical and basic research that led to the description of Flammer syndrome. It is narrated from a personal perspective. This research was initiated by the observation of an increased long-term fluctuation of visual fields in a subgroup of glaucoma patients. As these patients had strikingly cold hands, peripheral blood flow was tested with a capillary microscopy, and vasospastic syndrome (VS) was diagnosed. Further studies on these patients revealed frequently weakened autoregulation of ocular blood flow and increased flow resistivity in retroocular vessels. Their retinal vessels were more rigid and irregular and responded less to flickering light. Holistic investigation demonstrated low blood pressure, silent myocardial ischaemia, altered beat-to-beat variation, altered gene expression in the lymphocytes, slightly increased plasma endothelin level and increased systemic oxidative stress. This combination of signs and symptoms was better described by the term primary vascular dysregulation (PVD) than by VS. Subsequent studies showed additional symptoms frequently related to PVD, such as low body mass index, cold extremities combined with slightly increased core temperature, prolonged sleep onset time, reduced feelings of thirst, increased sensitivity to smell and also for certain drugs and increased retinal venous pressure. To better characterise this entire syndrome, the term Flammer syndrome (FS) was introduced. Most subjects with FS were healthy. Nevertheless, FS seemed to increase the risk for certain eye diseases, particularly in younger patients. This included normal-tension glaucoma, anterior ischaemic optic neuropathy, retinal vein occlusions, Susac syndrome and central serous chorioretinopathy. Hereditary diseases, such as Leber’s optic neuropathy or retinitis pigmentosa, were also associated with FS, and FS symptoms and sings occurred more frequent in patients with multiple sclerosis or with acute hearing loss. Further research should lead to a more concise definition of FS, a precise diagnosis and tools for recognizing people at risk for associated diseases. This may ultimately lead to more efficient and more personalised treatment.